Naphthoquinone Derivatives as Scaffold to Develop New Drugs for Tuberculosis Treatment - Halicki, Priscila C. B.; Ferreira, Laís A.; De Moura, Kelly C. G.; Carneiro, Paula F.; Del Rio, Karina P.; Carvalho, Tatiane dos S. C.; Pinto, Maria do C. F. R.; da Silva, Pedro E. A.; Ramos, Daniela F. (Frontiers in Microbiology, 2018)
Despite being a curable disease, tuberculosis (TB) remains a public health problem worldwide mainly due to lengthy treatment, as well as its toxic effects, TB/HIV co-infection and the emergence of resistant Mycobacterium tuberculosis strains. These barriers reinforcing the need for development of new antimicrobial agents, that ideally should reduce the time of treatment and be active against susceptible and resistant strains. Quinones are compounds found in natural sources and among them, the naphthoquinones show antifungal, antiparasitic, and antimycobacterial activity. Thus, we evaluated the potential antimycobacterial activity of six 1,4-naphthoquinones derivatives. We determined the minimum inhibitory concentration (MIC) of the compounds against three M. tuberculosis strains: a pan-susceptible H37Rv (ATCC 27294); one mono-resistant to isoniazid (ATCC 35822); and one mono-resistant to rifampicin (ATCC 35838); the cytotoxicity in the J774A.1 (ATCC TIB-67) macrophage lineage; performed in silico analysis about absorption, distribution, metabolism, and excretion (ADME) and docking sites. All evaluated naphthoquinones were active against the three strains with MIC between 206.6 and 12.5 μM, and the compounds with lower MIC values have also showed low cytotoxicity. Moreover, two naphthoquinones derivatives 5 and 6 probably do not exhibit cross resistance with isoniazid and rifampicin, respectively, and regarding ADME analysis, no compound violated the Lipinski’s rule-of-five. Considering the set of findings in this study, we conclude that these naphthoquinones could be promising scaffolds to develop new therapeutic strategies to TB.